Training in Compiling Simple Financial Reports at Warung Sambal Ijo Bang Juna, Pematangsiantar City - Juan Anastasia Putri; Eliza Arshandy; Christine Dewi Nainggolan; Kevin Indajang; Lenny Dermawan Sembiring; Acai Sudirman (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Training on the Preparation of Simple Financial Reports at Warung Sambal Ijo Bang Juna, Pematangsiantar City, is part of a community service effort to improve the capacity of micro-business management. This activity aims to provide understanding and skills in sharing knowledge and preparing simple but effective financial reports. This training was held to help shop owners manage their finances better and build a culture of constructive information sharing. According to the interview results, it is known that the understanding of Warung Sambal Ijo Bang Juna business owners regarding the preparation of simple financial reports increased by 90%. This activity not only provides direct benefits for Warung Sambal Ijo Bang Juna but also has the potential to empower other micro-businesses in Pematangsiantar City. With this training, business actors can be more efficient in managing finances and increasing collaboration, ultimately contributing to the growth and sustainability of micro-businesses in the area.